Synergetic effects of hybrid carbon nanostructured counter electrodes for dye-sensitized solar cells: A review - Samantaray M.R.; Mondal A.K.; Murugadoss G.; Pitchaimuthu S.; Das S.; Bahru R.; Mohamed M.A. (My University, 2025)
This article provides an overview of the structural and physicochemical properties of stable carbon-based nanomaterials and their applications as counter electrodes (CEs) in dye-sensitized solar cells (DSSCs). The research community has long sought to harvest highly efficient third-generation DSSCs by developing carbon-based CEs, which are among the most important components of DSSCs. Since the initial introduction of DSSCs, Pt-based electrodes have been commonly used as CEs owing to their high-electrocatalytic activities, thus, accelerating the redox couple at the electrode/electrolyte interface to complete the circuit. However, Pt-based electrodes have several limitations due to their cost, abundance, complicated facility, and low corrosion resistance in a liquid electrolyte, which further restricts the large-area applications of DSSCs. Although carbon-based nanostructures showed the best potential to replace Pt-CE of DSSC, several new properties and characteristics of carbon-CE have been reported for future enhancements in this field. In this review, we discuss the detailed synthesis, properties, and performances of various carbonaceous materials proposed for DSSC-CE. These nano-carbon materials include carbon nanoparticles, activated carbon, carbon nanofibers, carbon nanotube, two-dimensional graphene, and hybrid carbon material composites. Among the CE materials currently available, carbon-carbon hybridized electrodes show the best performance efficiency (up to 10.05%) with a high fill factor (83%). Indeed, up to 8.23% improvements in cell efficiency may be achieved by a carbon-metal hybrid material under sun condition. This review then provides guidance on how to choose appropriate carbon nanomaterials to improve the performance of CEs used in DSSCs. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.